Disinformation and digital influencing after terrorism: spoofing, truthing and social proofing. Issue 2 (15th March 2021) - Innes, Martin; Dobreva, Diyana; Innes, Helen
ABSTRACT: This article explores how digital communications platforms are used in the aftermath of terrorist attacks to amplify or constrain the wider social impacts and consequences of politically motivated violence. Informed by empirical data collected by monitoring social media platforms following four terrorist attacks in the UK in 2017, the analysis focusses on the role of 'soft facts' (rumours/conspiracy theories/fake news/propaganda) in influencing public understandings and definitions of the situation. Specifically, it identifies three digital influence engineering techniques – spoofing, truthing and social proofing – that are associated with the communication of misinformation and disinformation. After configuring these concepts, the authors consider their implications for policy and practice development, concluding that, to date, possibilities for evidence-informed post-event preventative interventions have been relatively neglected in the formulation of counter-terrorism strategies. They recommend more attention be paid to how strategic communications interventions can counteract the effects of misinformation and disinformation, and thus mitigate the wider public harms induced by terror events.